2009
DOI: 10.1111/j.1469-8749.2008.03215.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment severity selectively affects the control of proximal and distal components of reaching movements in children with hemiplegic cerebral palsy

Abstract: This study explored proximal‐to‐distal components during goal‐directed reaching movements in children with mild or moderate hemiplegic cerebral palsy (HCP); [seven females, four males; mean age 8y 6mo; SD 27mo], compared with age‐matched, typically developing children (seven females, five males; mean age 8y 3mo [SD 25mo]. Severity of HCP was assessed following the approach of Claeys et al. Optoelectronic registrations were made during unimanual reaching‐to‐grasp and reaching‐to‐hit movements with both the affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 28 publications
(71 reference statements)
3
13
0
Order By: Relevance
“…Vertical lines indicate standard deviations. Asterisk indicates significant difference (p < 0.05) atypical motion patterns in individuals with CP have generally been attributed to the effects of the endured brain injury and considered as impeding on optimal performance (e.g., Duque et al 2003;Domellöf et al 2009). However, by varying the conditions under which the task was to be performed, our results indicated that the relation between task performance and underlying joint kinematics was less univocal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vertical lines indicate standard deviations. Asterisk indicates significant difference (p < 0.05) atypical motion patterns in individuals with CP have generally been attributed to the effects of the endured brain injury and considered as impeding on optimal performance (e.g., Duque et al 2003;Domellöf et al 2009). However, by varying the conditions under which the task was to be performed, our results indicated that the relation between task performance and underlying joint kinematics was less univocal.…”
Section: Discussionmentioning
confidence: 99%
“…However, both CP and TD teenagers demonstrated a larger contribution of trunk movement when facing more challenging task conditions. The overall pattern of results indicated that optimal performance (Duque et al 2003;Domellöf et al 2009). However, patterns of joint motion considered characteristic of CP are also noticeable when TD individuals are (a) submitted to challenging upper limb task conditions (Van der Kamp and Steenbergen 1999) or (b) forced to use their non-preferred upper limb for task performance (Steenbergen et al 1995).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Reduced hip adduction [1,2] and increased external rotation have been observed during stance [2]. These changes have been linked to changes in hip contact force [2].…”
mentioning
confidence: 99%